Current dorsal myelographic column and dural diameter reduction rules do not apply at the cervicothoracic junction in horses. Issue 6 (11th July 2018) - Estell, Krista; Spriet, Mathieu; Phillips, Kathryn L.; Aleman, Monica; Finno, Carrie J.
Abstract: Previously published myelographic studies do not report findings at the junction between the seventh cervical (C7) and first thoracic vertebrae (T1). Modern digital radiographic equipment allows improved visualization of C7‐T1. Based on clinical experience, we hypothesized that 50% reduction of the dorsal myelographic column or 20% reduction of the dural diameter, criteria commonly used as a supportive finding for spinal cord compression in the cervical vertebral column, do not apply at C7‐T1. A myelographic study was performed on 12 healthy, neurologically normal horses. Our hypothesis was confirmed; using established criteria eight of 12 horses would have been classified as having evidence of spinal cord compression at C7‐T1. The dorsal myelographic column reduction at C7‐T1 was 48 ± 12%, while the C6‐C7 dorsal myelographic column reduction was 33 ± 17% (mean ± standard deviation) ( P  = 0.010). The dural diameter reduction at C7‐T1 (22.0 ± 6.7%) was significantly greater than the dural diameter reduction at C6‐C7 (13.2 ± 9.5%) ( P  = 0.0007). Further measurements and comparisons suggested that the apparent greater reduction of dorsal myelographic column and dural diameter at C7‐T1 was due to larger intravertebral measurements at C7 rather than smaller intervertebral values at C7‐T1. Based on these findings, alternative criteria should be used at C7‐T1 when assessing clinical cases for cervical stenotic myelopathy. Reduction of the dorsal myelographic column by 60% or of the dural diameter by 30% would avoid high numbers of false positive myelographic cases at C7‐T1.